Islam through Western Eyes - Zeina Sleiman (International Institute of Islamic Thought, 2016)
Jonathan Lyons’ Islam through Western Eyes takes a critical and historical approach to understanding the anti-Islam discourses that continue to emerge across North America and Europe. His main argument is that their origins can be traced back to the Crusades and that the current Islamophobic climate has been in the production since then. Thus an inherent anti-Islam discourse has been ingrained into the western imagination, and its effects are still being seen today. In the introduction, the author notes that the answer to understanding much of this western Islamophobic movement has been in the making since the fifteenth century anti-Islam discourse as it relates to the Crusades. Lyons notes that we need to develop a deeper understanding of the history of this discourse in order to fight its modern version and to understand the causes of the current Islamophobic climate. This certainly sheds a more complex light on many of the issues facing Muslims in Europe and North America, and gives readers a new angle from which they should understand and interpret this growing sentiment. The book is divided into five main chapters following the introduction. The first is essentially a chapter on methodology, which delves deeper into Foucault’s critical theories on discourse and power. Lyons particularly focuses on Foucault’s Archeology of Knowledge, in which he argues that certain forms of knowledge are privileged over others in order to create a larger narrative about a particular topic or group of people. The author clearly takes a post- ...